Agricultural growth and investment options for poverty reduction in Nigeria - Diao, Xinshen; Nwafor, Manson; Alpuerto, Vida; Akramov, Kamiljon T.; Salau, Sheu (International Food Policy Research Institute, 2010)
This study uses an economy-wide, dynamic computable general equilibrium (DCGE) model to analyze the ability of growth in various agricultural subsectors to accelerate overall economic growth and reduce poverty in Nigeria over the next years (2009-17). In addition, econometric methods are used to assess growth requirements in agricultural public spending and the relationship between public services and farmers' use of modern technology. The DCGE model results show that if certain agricultural subsectors can reach the growth targets set by the Nigerian government, the country will see 9.5 percent annual growth in agriculture and 8.0 percent growth of GDP over the next years. The national poverty rate will fall to 30.8 percent by 2017, more than halving the 1996 poverty rate of 65.6 percent and thereby accomplishing the first Millennium Development Goal (MDG1). This report emphasizes that in designing an agricultural strategy and prioritizing growth, it is important to consider the following four factors at the subsectoral level: (i) the size of a given subsector in the economy; (ii) the growth-multiplier effects occurring through linkages of the subsector with the rest of the economy; (iii) the subsector-led poverty reduction-growth elasticity; and (iv) the market opportunities and price effects for individual agricultural products. In analyzing the public investments that would be required to support a 9.5 percent annual growth in agriculture, this study first estimates the growth elasticity of public investments using historical spending and agricultural total factor productivity (TFP) growth data. The results show that a 1 percent increase in agricultural spending is associated with a 0.24 percent annual increase in agricultural TFP. With such low elasticity, agricultural investments must grow at 23.8 percent annually to support a 9.5 percent increase in agriculture. However, if the spending efficiency can be improved by 70 percent, the required agricultural investment growth becomes 13.6 percent per year. The study also finds that investments outside agriculture benefit growth in the agricultural sector. Thus, assessments of required growth in agricultural spending should include the indirect effects of nonagricultural investments and emphasize the importance of improving the efficiency of agricultural investments. To further show that efficiency in agricultural spending is critically important to agricultural growth, this study utilizes household-level data to empirically show that access to agricultural services has a significantly positive effect on the use of modern agricultural inputs.